Does maternal body mass index impact on the antenatal detection of congenital anomalies?. (7th June 2011) - Best, K E; Tennant, P W G; Bell, R; Rankin, J
Abstract : Background: Raised maternal body mass index (BMI) is associated with an increased risk of congenital anomaly. This may partly be explained by differences in antenatal detection of anomalies and hence, varied termination rates. This study aimed to investigate the association between maternal BMI and antenatal detection of congenital anomaly in a population-based case-series from Northeast England. Methods: Data on congenital anomalies occurring in singleton pregnancies booked and delivered in five maternity units in Northeast England during 2003–2005 were linked with data from the Northern Congenital Abnormality Survey. Adjusted ORs (aORs) for antenatal detection (of any anomaly) according to maternal BMI were estimated using logistic regression. Results: 961 congenital anomaly cases were reported among 40 934 pregnancies, a prevalence of 224 (95% CI 208 to 237) per 10, 000 births. Antenatal detection of any anomaly occurred in 429 (44.6%) cases. The odds of detection significantly decreased with increasing maternal BMI (aOR, per kg/m 2 =0.97, 95% CI 0.94 to 0.99; p=0.018). However, there was no evidence that termination of pregnancy was associated with maternal BMI (aOR=0.96, 95% CI 0.93 to 1.01; p=0.08). Overall, 416 (43.4%) cases were associated with cardiovascular anomalies (prevalence: 102 (95% CI 92 to 112) per 10 000 births). In 89 (21.4%) of these, an anomaly of the cardiovascular system was detected antenatally, and the odds of detection decreased significantly with increasing maternal BMI (aOR, per kg/m 2 =0.93, 95% CI 0.87 to 0.99; p=0.02). Conclusion: Antenatal detection of a congenital anomaly decreases with increasing maternal BMI. This has implications for the scanning and counselling of overweight and obese pregnant women.